2012
DOI: 10.1126/science.1216697
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Spin Polarization of the ν = 5/2 Fractional Quantum Hall State

Abstract: The fractional quantum Hall (FQH) effect at filling factor ν = 5/2 has recently come under close scrutiny, as its ground state may possess quasi-particle excitations obeying nonabelian statistics, a property sought for topologically protected quantum operations. However, its microscopic origin remains unknown, and candidate model wave functions include those with undesirable abelian statistics. We report direct measurements of the electron spin polarization of the ν = 5/2 FQH state using resistively detected n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
165
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 169 publications
(188 citation statements)
references
References 48 publications
23
165
0
Order By: Relevance
“…Although the experimental error depends on an uncertainty of ±5% in w, it is estimated to be about 0.32 MHz·nm for the ν = 2/3 state at 6.4 T, 6 which is translated into α full ∼ 0.38 MHz·nm at B = 7.65 T used in the present work. Meanwhile, it is shown that a tiny change of 0.3% in the in-plane electron density triggers the spin phase transition.…”
Section: S2: Model Calculation Of Ner Spectral Lineshapementioning
confidence: 76%
“…Although the experimental error depends on an uncertainty of ±5% in w, it is estimated to be about 0.32 MHz·nm for the ν = 2/3 state at 6.4 T, 6 which is translated into α full ∼ 0.38 MHz·nm at B = 7.65 T used in the present work. Meanwhile, it is shown that a tiny change of 0.3% in the in-plane electron density triggers the spin phase transition.…”
Section: S2: Model Calculation Of Ner Spectral Lineshapementioning
confidence: 76%
“…The resonance at = 1, for instance, exhibits a strong asymmetry, whereas at = 2 the resonance is rather symmetric. This behavior can be understood as a consequence of the finite width of the electron wavefunction in the direction perpendicular to the quantum well as described below [159,184]. …”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, we deem the calibration at = 5 ⁄3 reliable. A spin polarization * ( = 1) < 1 is not surprising in view of the skyrmions present in this region (see section 3.2.2) and has been observed before [159,193]. In turn, using * ( = 1) = 1 as a calibration would imply * ( = 5 ⁄3) > 1/3, i.e.…”
Section: Discussion Of the Nmr Lineshapementioning
confidence: 99%
See 2 more Smart Citations